HUBUNGAN ANTARA SELF EFFICACY, MOTIVASI BERPRESTASI, DAN KEMANDIRIAN DENGAN HASIL BELAJAR MATEMATIKA SEKOLAH DASAR - Muliyanti, Muliyanti; Asrori, Muhammad; Jamiah, Yulis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe pupose of this research is to describe the relationship between: 1) self efficacy with study result mathematics, 2) achievement motivation with study result 3) independence with study result mathematics, 4) self efficacy and achievement motivation together with study result mathematics, 5) self efficacy and independence together with study result mathematics, 6) achievement motivation and independence together with study result mathematics, 7) self efficacy, achievement motivation, independence together with mathematics 5th Grade of 06 Public Elementary School, South Pontianak. This research which was conducted a descriptive method with a quantitative approach. Theresearch type is correlational study. This research was conducted in the A5thandB5thof 06 Public Elementary School, South Pontianak. The subject ofÂ thisÂ population research with total number 50 students. Data collection was carried out using a questionnaire instrument. Data analysis techniques were performed with descriptive statistical analysis, while to determine the relationship between the three variables, namely self efficacy, achievement motivation and independence with mathematics study resultused through calculations with simple correlations and multiple correlations. The results showed that there was a positive and significant relationship between: 1) self efficacy with study result mathematics of 0.450, 2) achievement motivation with study result mathematics of 0.573, 3) independence with study result mathematics of 0.543, 4) self efficacy and achievement motivation together with study result mathematics of 0.595, 5) self efficacy and independence together with study result mathematics of 0.600, 6) achievement motivation and independence together with study result mathematics of 0.640, 7) self efficacy, achievement motivation, independence together with mathematics of 0.651.Â Keywords: Self Efficacy, Achievement Motivation, Independence, Mathematics Learning Outcomes